Pemetaan desa partisipatif dan penyelesaian konflik batas: studi kasus di desa-desa daerah aliran sungai Malinau, January s/d Juli 2000 - Anau, N.; Heist, M. van; Iwan, R.; Limberg, G.; Sudana, I.M.; Wollenberg, Eva Karoline (Center for International Forestry Research, 2001)
CIFOR's ACM program has been carrying out participatory action research with local communities to devise models for forest management by multiple stakeholders. One of the early requests by communities has been for the mapping of their villages. This report describes the facilitation team's observations during the process of mapping these territories (villages along the Malinau river, Kalimantan, Indonesia). Central theme is the question what caused conflicts within and between villages and how were these handled and overcome by the communities. The role that the participatory mapping process played in identifying as well as solving the conflicts is discussed. After a general overview and analysis of the situation, each village is also described in more detail: background information, description of the conflicts and approach to solving them.